1987
DOI: 10.1021/bi00386a055
|View full text |Cite
|
Sign up to set email alerts
|

Backbone dynamics of a model membrane protein: assignment of the carbonyl carbon carbon-13 NMR resonances in detergent-solubilized M13 coat protein

Abstract: The major coat protein of the filamentous bacteriophage M13 is a 50-residue amphiphilic polypeptide which is inserted, as an integral membrane-spanning protein, in the inner membrane of the Escherichia coli host during infection. 13C was incorporated biosynthetically into a total of 23 of the peptide carbonyls using labeled amino acids (alanine, glycine, lysine, phenylalanine, and proline). The structure and dynamics of carbonyl-labeled M13 coat protein were monitored by 13C nuclear magnetic resonance (NMR) sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

1989
1989
2007
2007

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 42 publications
1
16
0
Order By: Relevance
“…These observations are at variance with results obtained in another time-resolved fluorescence study by Datema et al (1987a). As the fluorescence intensity and anisotropy decay behavior in detergent micelles (sodium dodecyl sulfate) observed by Datema et al (1987a) are generally similar to our data in DOC [these two detergents produce substantially similar protein conformational properties (Makino et al, 1975;Nozaki et al, 1978;Henry et al, 1986Henry et al, , 1987], the origin of the different results obtained in phospholipid bilayers is apparently intrinsic to the lipid/protein preparations. Two potentially significant differences in the 13-CP/phospholipid preparations can be identified: Datema et al (1987a) used a slightly different lipid composition (20% w/w dimyristoylphosphatidic acid in DMPC) and a different protein incorporation method (detergent dialysis).…”
Section: Plots Of 2 (Tablesupporting
confidence: 75%
See 2 more Smart Citations
“…These observations are at variance with results obtained in another time-resolved fluorescence study by Datema et al (1987a). As the fluorescence intensity and anisotropy decay behavior in detergent micelles (sodium dodecyl sulfate) observed by Datema et al (1987a) are generally similar to our data in DOC [these two detergents produce substantially similar protein conformational properties (Makino et al, 1975;Nozaki et al, 1978;Henry et al, 1986Henry et al, , 1987], the origin of the different results obtained in phospholipid bilayers is apparently intrinsic to the lipid/protein preparations. Two potentially significant differences in the 13-CP/phospholipid preparations can be identified: Datema et al (1987a) used a slightly different lipid composition (20% w/w dimyristoylphosphatidic acid in DMPC) and a different protein incorporation method (detergent dialysis).…”
Section: Plots Of 2 (Tablesupporting
confidence: 75%
“…This conclusion is supported by the similarity of the corresponding steady-state fluorescence spectra (Figure 1). Although conformational multiplicity of M13-CP has previously been inferred from CD (Nozaki et al, 1978;Williams & Dunker, 1977;Fodor et al, 1981), Raman (Fodor et al, 1981;Dunker et al, 1982), and NMR (Wilson & Dahlquist, 1985) spectroscopy, the consensus of physical studies of the structure and dynamics of M13-CP to date appears to be that the stable micelle and membrane-associated forms are substantially similar (Nozaki et al, 1976;Chamberlain et al, 1978;Henry et al, 1986Henry et al, , 1987Leo et al, 1987). Our fluorescence decay data and steady-state spectra appear in accordance with this consensus in respect of the region adjacent to the tryptophan residue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These lysines may "pull in" the micellar surface to produce an optimal arrangement for electrostatic interactions between the sulfate head groups of the SDS and the positively charged lysyl NH3+. Henry et al (1987) also suggested a stable complex of the lysines and the negatively charged head group of the surfactant molecules based on the results of digestion on the C-terminus of gVIIIp using proteinase K. It is known from other NMR studies on gVIIIp in membrane environments that K40, K43, and K44 are near the surface of the bilayer (Sanders et al, 1991). Assuming that the head group of the stearate molecule interacts with the positive charges of the lysines, the position of the 5-doxyl group is such that it will have a large influence on residue 38.…”
Section: Resultsmentioning
confidence: 99%
“…GVIIIp is a small protein (50 residues, molecular mass = 5.2 kDa) that, when complexed with small micelles, e.g., sodium dodecyl sulfate (SDS), rotates rapidly enough to give reasonably well-resolved NMR spectra. This sytem has been studied for many years, but until recently, the NMR experiments were mostly restricted to measurements of the dynamics and solvent exchange rates of amide protons (Cross & Opella, 1980;O'Neil & Sykes, 1988;Henry et al, 1987;Henry & Sykes, 1990).…”
mentioning
confidence: 99%